Comparative effects of three 1,4-dihydropyridine derivatives [OSI-1210, OSI-1211 (etaftoron), and OSI-3802] on rat liver mitochondrial bioenergetics and on the physical properties of membrane lipid bilayers: Relevance to the length of the alkoxyl chain in positions 3 and 5 of the DHP ring - Fernandes, Maria A. S. (2008)
The 1,4-dihydropyridines OSI-1210, OSI-1211 (etaftoron), and OSI-3802 are compounds with similar chemical structure. They differ by the length of the alkoxyl chain in positions 3 and 5 of the dihydropyridine (DHP) ring and by their pharmacological action characteristics. However, as far as we know, a clear relationship between the effects of these compounds and the length of the alkoxyl chain in positions 3 and 5 of the DHP has not been established. The goal of this study was to compare the influence of OSI-1210, OSI-1211 (etaftoron), and OSI-3802 on rat liver mitochondrial bioenergetics and on the physical properties of membrane lipid bilayers, correlating their actions with the length of the alkoxyl chain in positions 3 and 5 of the DHP ring. Using either glutamate/malate or succinate as respiratory substrates, all the compounds, in concentrations of up to 500 [mu]M, depressed state 3 and uncoupled respiration, respiratory control (RCR) and ADP/O ratios, and phosphorylation rate, whereas state 4 respiration was stimulated. However, the stimulatory effect on state 4 induced by OSI-3802, the compound with the longest chain in positions 3 and 5 of the DHP ring, as well as its inhibitory effects on RCR and ADP/O ratios and phosphorylation rate were more pronounced than that induced by OSI-1210 and OSI-1211 (etaftoron), the compounds with the shortest and intermediate chains, respectively. Moreover, OSI-3802 maximized state 4 stimulation and minimized RCR and ADP/O ratios, and phosphorylation rate at a concentration of 100 [mu]M, whereas low graduate effects were detected with OSI-1210 and OSI-1211 (etaftoron) for concentrations of up to 500 [mu]M. At low concentrations (<=30 [mu]M), OSI-3802, like its analogue OSI-1212 (cerebrocrast), reduced the phase transition temperature, the cooperative unit size, and the enthalpy associated with the phase transition temperature of dimyristoylphosphatidylcholine (DMPC) membrane bilayers. A good correlation was established between the effects of 200 [mu]M OSI-1210, OSI-1211 (etaftoron), and OSI-3802 on glutamate/malate- and succinate-dependent RCR of rat liver mitochondria and on the enthalpy change ([Delta]H) for the thermotropic profile of DMPC membrane bilayers at a 0.2 drug/DMPC molar ratio, indicating that the changes induced by these compounds on both mitochondrial membrane integrity and physical properties of DMPC membrane bilayers are strongly related to the length of the alkoxyl chain in positions 3 and 5 of the DHP ring. A putative relationship between membrane physical perturbation, bioenergetics impairment and the molecular characteristics of the compounds will be established as an approach to better understand their differentiated toxicological and pharmacological actions.